From education planning and the limits of state intervention - Márquez-Domínguez, Yolanda (Avances en Supervisión Educativa, 2021)
The analysis of this essay will be from a political and ideological perspective where the most recent changes in education have been presided over by a rationalization of scholarly systems in line with an interpretation of a "world order" which conservative ideologies present as the only possible one - that is to say, the hegemony of marketplace ideology and Neoliberalism. It is against this background, and from a political/pedagogical point of view that this paper is written. The relation between Education and the State is a complex matter which has gone through different stages, and the process of allocation of responsibilities has been such that the State has claimed a role as the sole legitimate owner of Education. This is both realized and justified from within a neoliberal milieu that promotes policies which consider results as almost exclusively relevant. The hierarchical model is questioned as well as the presumed orthodoxy of everyday practice; and last but not least the agenda of privatization hidden within a neoliberal model, that involves changes in educational practice, is also called into question.